Goethe yearbook : publications of the Goethe Society of North America. - Daub, Adrian; Krimmer, Elisabeth, 1967- (JSTOR EBA., 2015)
Cutting-edge scholarly articles on diverse aspects of Goethe and the Goethezeit, featuring in this volume a special section on environmentalism.